THE HUMAN WITH A SHEEP’S HEAD AS A SOURCE OF INSPIRATION IN PAINTING FOR THE DEVELOPMENT OF LOCAL CULTURE IN GARUT REGENCY - Hapana, Reni; Athian, Muhammad Rahman (Universitas Negeri Semarang, 2025)
This study project is a visualization of the various local cultures found in Garut Regency through surrealist-style painting. The artworks were created using the Scumbling technique. Surrealist painting is a style that emphasizes imagination and imagery drawn from the subconscious mind. In the process of creating this study project, the author produced ten artworks, each representing a different subject as a visual expression aimed at developing the local culture of Garut Regency. These works serve to provide clear and accessible cultural information. As such, the artworks are intended to be easily understood by the wider public, while also inviting appreciators and the broader community to see, feel, and comprehend the meaning and essence of each local cultural element of Garut. Through these paintings, the author hopes to inspire and motivate future generations to develop the potential of their local culture so that it may be accepted and recognized more broadly. The local cultural values visualized in these artworks can serve as valuable sources for character and moral education. Through painting, art can become a powerful learning tool that enhances creativity and imagination, and acts as a tangible example within both educational and life contexts.